[tex]y = -x^2 + 12x - 11[/tex]
f(x) in intercept form
General equation of intercept form of quadratic equation is
[tex]y=a(x-b)(x-c)[/tex]
To get intercept form we factor the right hand side of the given equation
[tex]y = -x^2 + 12x - 11[/tex]
Factor out -1
[tex]y = -1(x^2 - 12x + 11)[/tex], factor x^2 - 12x +11
[tex]y = -1(x-11)(x-1)[/tex] -------> Intercept form
To find zeros of the function, we replace y with 0
then we set each factor =0 and solve for x
0=-1(x-11)(x-1)
x-11 =0 and x-1=0
x= 11 and x=1
Now we subtract the zeros
11-1 = 10
the wolf leaped about 10 meters (units not mentioned in the question)